ANALISIS PENERAPAN PSAK 24 TENTANG IMBALAN KERJA PADA PT VANDIKA ABADI - Rumimper, Gisela; Alexander, Stanly; Warongan, Jessy (Universitas Sam Ratulangi, 2017)
The fast growing business world is demanding every company or business entity to be more competitive and continue to strive to achieve the goals set. Object in this research is PT VANDIKA ABADI as one of the companies engaged in the provision of labor services. The purpose of this study is to find out whether PT Vandika Abadi has applied PSAK 24 on employee benefits. This type of research is a type of descriptive-qualitative research, which is a method used to describe the actual based on what appears. Usually done an analysis that can provide a clearer picture of the object under study, and draw conclusions. The results of the research can be seen that PT Vandika Abadi has implemented some activities that are in accordance with the scope of PSAK24 regarding post-employment benefits and short-term employee benefits. In accordance with PSAK 24, recognition and measurement of short term employee benefits are recorded at the expense at the time the employee is payable while the post-employment benefits expense is recognized and measured based on contributions paid by the company. PT Vandika Abadi also provides post-employment benefits that are benefits to its employees, employee benefits are payments and services that protect and supplement salaries.Keywords: PSAK 24, Short-term Employee Benefit, Post Employment Benefit